PENGGUNAAN EKSTRAK DAUN KATUK (Sauropus androgunus L. Merr) SEBAGAI BAHAN PE,NGA-WET ALAMI DAGINGSAPI SEGAR - Bambang Kuntoro; Irdha Mirdhayati, dan; Triani Adelina (State Islamic University of Sultan Syarif Kasim Riau, 2007)
Meat is high nutrient food material because it consist much protein, fat, mineral and other substances that needed by human body. The .Meat nutrient pel'centage is the appropriate media for the growth of microorganism especially bacteria. The microorganism activity can decrease meat quality. Hence, itneed exact treatment for keep the meat quality. One of used the treatment is adding extract of the Sauropus and1'ogJnus (L.) Me1'1'. Extract of the Sauropus androgynus constitute material that consist of antibacterial compounq. Content OrSO:UT0pu5 androgyrius characteristk is oxide bacteria that having ability to remove sone bacteria sm;has seskuite,rna add. alkaloid papaVerlllt tanin,.. saponiri,. fiavonoiq, mineral salt, other compounds,The purpose of this research is to determine influence the meat submersion within e).